Thyroid status in the combination of atrial fibrillation with subclinical thyrotoxicosis - Rakhmatullov, Ruslan F; Rakhmatullov, Artur F; Rakhmatullov, Fagim K; Burmistrova, Larisa F; Moiseeva, Inessa J (Bangladesh Journal of Medical Science, 2019)
Objective: To study the factors in the development of atrial fibrillation in patients with subclinical hyperthyroidism on the background of angina pectoris as a result of a comprehensive analysis of the electrocardiographic and echocardiographic indicators of the heart, thyroid volume, thyroid hormone levels and lipid profile. Materials and Methods: The risk factors for atrial fibrillation (AF) were studied in patients with subclinical hyperthyroidism (SH) and angina pectoris. It was revealed that the starting factor for the occurrence of AF in patients with subclinical hyperthyroidism is a shift in the reference values of thyroid hormones. It was established that the total depression of the ST segment reflects the degree of coronary reserve in patients with AF on the background of SH. Results and Discussion: It has been shown that in patients with subclinical hyperthyroidism, there is a normal level of total cholesterol and LDLP, a low level of triglycerides and atherogenicity, and a high level of HDLP. When combined with subclinical hyperthyroidism and paroxysmal AF, there is an increase in the level of total cholesterol, LDLP, TG, atherogenicity and decreased HDLP. Conclusion: It has been proven that diastolic dysfunction of the left ventricle of the first type is formed on the background of SH. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.402-410